Advertising Strategy and Brand Building - Yuananda, Dewantari Puteri; Huda, Miftahul (Universitas Serambi Mekkah, 2024)
Communicating a brand message to the target audience is an important component of a marketing strategy. efficiency. Effective marketing communications occur when messages can be communicated precisely, easily understood, and without confusion. stay consistent across all marketing channels. Advertising is the main element in marketing strategy. Advertising aims to influence consumers to make purchases and increase company sales figures. So that advertising can achieve optimal results, advertising strategy is something that cannot be ignored. Marketing strategy is a strategy designed to increase sales of certain products or services, attract new consumers, and encourage existing consumers to make more frequent purchases, and so on. the most important thing for every brand. Advertising strategy is part of a brand's marketing plan, so it needs to be in accordance with company goals. It's also worth considering branding, tone, and brand identity so that the user experience isn't disrupted by incongruent elements. Advertising strategies have great importance because they provide guidance in achieving marketing goals. It investigates factors such as market conditions, key audience desires, and competitor activity.